Interhemispheric transfer time in sportsmen - Semprini, G.; Coggi, D.; Corballis, M. C. (Journal of Motor Behavior, 2013)
The authors` aim was to compare interhemispheric transfer time between 2 groups: highly skilled sportsmen and control subjects. Left- and right-handed individuals were included in the study. The Poffenberger paradigm was used to measure the crossed-uncrossed difference, representing the time to transfer information from one hemisphere to the other. No difference in lateralitywas found, but the results revealed a greater crossed-uncrossed difference in the skilled sportsmen than in the controls. The authors suggest that this may be due to more highly developed withinhemisphere integration of inputs and outputs, at the expense of cross-hemisphere integration.